2021
DOI: 10.1002/dac.4985
|View full text |Cite
|
Sign up to set email alerts
|

Physical layer secure key generation with nonlinear preprocessing of RSS for power constraint wireless networks

Abstract: Summary There has been growing attention in physical layer security (PLS) techniques for wireless networks. PLS techniques are based on physical layer characteristics and are less computationally complex than traditional cryptographic approaches, which work on higher layers of networks. Physical layer key generation (PLKG) is one of the prominent key based PLS techniques that exploits reciprocity and randomness of wireless fading channel to establish secure communication between two transceivers. PLKG system c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The Llyod Max quantizer has better randomness and a reduced BDR. Ravindra Sharma et al 32 demonstrated a nonlinear preprocessing solution for future IoT and energy‐aware networks that surpasses existing methods at low SNR levels. They employ A‐law and μ‐law as nonlinear preprocessing approaches to improve network performance.…”
Section: Related Workmentioning
confidence: 99%
“…The Llyod Max quantizer has better randomness and a reduced BDR. Ravindra Sharma et al 32 demonstrated a nonlinear preprocessing solution for future IoT and energy‐aware networks that surpasses existing methods at low SNR levels. They employ A‐law and μ‐law as nonlinear preprocessing approaches to improve network performance.…”
Section: Related Workmentioning
confidence: 99%
“…Works well only for low SNR values of 20dB. [19] When the harsh indoor environment, the proposed indoor positioning algorithm combines the use of filters as a preprocessing method with the implementation of sector Preprocessing using Gaussian filter and mean filter.…”
Section: Gaussian and Kalman Filteringmentioning
confidence: 99%
“…The scope of WMSN applications includes monitoring of indoor and outdoor environments [3], IoT-based smart agriculture [4] and object tracking [5]. The transport layer [6,7], the network layer [8], the physical layer [9] and the media access control layer [10,11] have been extensively researched in WMSNs.…”
Section: Introductionmentioning
confidence: 99%